Application of the Unified Theory of Acceptance & Use of Technology to Internet Banking - Gorecha, Anoop (2006)
Developing propositions for Internet account management is very costly, especially with irrefutable evidence that consumers don't abandon traditional channels, dormancy rates of 50%, and decreasing loyalty. Despite transactional costs savings hyped at 98%-99% of branch costs the return on investment is insufficient if based purely against cost-savings. For Internet banking to be successful, banks need to cross the adoption chasms and require adoption and regular usage by the majority of 'indifferent consumers'. Attempts to understand adoption of Internet banking have typically focussed on the attributes of adopters rather than the perceived benefits of the innovation itself. Technology acceptance models study the adoption decision itself in order to identify and test its underlying constructs. But with competing models, researchers are required to largely ignore contributions from other models or create hybrids that may limit comparison. Venkatesh et al (2003) propose the Unified Theory of Acceptance & Usage of Technology (UTAUT) integrates the strongest predictors of adoption from eight influential models. UTAUT has been studied in various technology applications and the primary purpose of this paper is to empirically validate its research model to the case of Internet banking. The findings suggest that performance expectancy, effort expectancy and behavioural intention are significant predictors for usage and draws out practical implications. The research also analyses socio-demographic attributes, patterns of Internet usage at home and work / college, and attitudes towards financial management. The findings suggest that there are no statistically significant differences between usage of Internet banking and ethnicity or financial attitudes. The demographic profiles match the commonly accepted view that users are generally, younger, more affluent and better educated. Access to high speed Internet connection was also widespread and individuals equally likely to access Internet banking from work or home.